Para se ver na vitrine: o uso da história oral e das arqueologias das mídias nas pesquisas sobre o cinema pioneiro - Daronco, Marilice (2023)
This article combines multidisciplinary methodologies, such as oral history and studies related to media archaeologies, to investigate the “Showcase Movie,” exhibitions made in the 1930s, in the interior of Rio Grande do Sul, by the Ukrainian photographer Sioma Breitman (1903-1980) at the showcase of his photographic studio, Casa Aurora. By building a narrative about a media hitherto unknown, we propose a discussion about memory, forgetting, and the importance of new perspectives for the history of media, especially cinema.